MEASURES FOR THE DEVELOPMENT OF TOURISM DIGITALIZATION IN THE TERRITORY OF KARAKALPAKSTAN - Matyakupova Madina Quzibay qizi (Web of Journals Publishing, 2025)
Efforts to develop domestic and international tourism in Uzbekistan have not excluded the territory of Karakalpakstan. Therefore, in order to effectively utilize the tourism potential of the Republic of Karakalpakstan, increase the region’s attractiveness for domestic and international tourism markets, improve the infrastructure of tourism, cultural heritage, arts and culture, introduce new tourism services, expand the range of national handicraft products, and create new jobs in the sector, numerous initiatives have been implemented.
Keywords: Tourism sector, Digital services, Tourism infrastructure, Tourist services, Customer-oriented services, Virtual Reality (VR), Augmented Reality (AR), Tourism development, Digital Twin.